1998
DOI: 10.1006/dbio.1998.9005
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric Protein B Null Mice Are Viable with No Apparent Abnormalities

Abstract: The centromere protein B (CENP-B) is a centromeric DNA/binding protein. It recognizes a 17-bp sequence motif called the CENP-B box, which is found in the centromeric region of most chromosomes. It binds DNA through its amino terminus and dimerizes through its carboxy terminus. CENP-B protein has been proposed to perform a vital role in organizing chromatin structures at centromeres. However, other evidence does not agree with this view. For example, CENP-B is found at inactive centromeres on stable dicentric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 37 publications
1
77
0
Order By: Relevance
“…CENP-E, CENP-F, INCENP, survivin, MCAK, ZWINT-1, ZW10, MAD-1, MAD-2, BUB1, BUBR1, and BUB3) associate with the centromere during specific stages of the cell cycle. Constitutive proteins CENP-A, CENP-C, and CENP-H are essential for correct kinetochore assembly and function as evidenced by a lethal phenotype in gene knockout and antibody/RNA inhibition studies in mouse, worm, and chicken DT40 cells (13)(14)(15)(16)(17)(18)(19)(20)(21), whereas CENP-B appears to be functionally redundant for centromere activity (22)(23)(24). Numerous gene knockout and inhibition studies have demonstrated that many of the transient proteins have essential roles in normal mitotic functions, such as INCENP, survivin, CENP-E, BUB3, and MAD2 (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…CENP-E, CENP-F, INCENP, survivin, MCAK, ZWINT-1, ZW10, MAD-1, MAD-2, BUB1, BUBR1, and BUB3) associate with the centromere during specific stages of the cell cycle. Constitutive proteins CENP-A, CENP-C, and CENP-H are essential for correct kinetochore assembly and function as evidenced by a lethal phenotype in gene knockout and antibody/RNA inhibition studies in mouse, worm, and chicken DT40 cells (13)(14)(15)(16)(17)(18)(19)(20)(21), whereas CENP-B appears to be functionally redundant for centromere activity (22)(23)(24). Numerous gene knockout and inhibition studies have demonstrated that many of the transient proteins have essential roles in normal mitotic functions, such as INCENP, survivin, CENP-E, BUB3, and MAD2 (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Several of these genes have been knocked out in mice to determine their role in the prevention of aneuploidy. Whereas homozygous CENPB loss resulted in no overt phenotypes other than slightly lower testis and body weights (Hudson et al, 1998, Kapoor et al, 1998, Perez-Castro et al, 1998, disruption of CENPA or CENPC led to embryonic lethality in early stages of embryogenesis (E3.5-E6.5). The early embryos show micronuclei, a lowered mitotic index (indicative of mitotic delay), and enlarged nuclei (suggestive of tetraploid cells).…”
Section: Loss Of Centromeric (Cenp) Genes Frequently Causes Embryonicmentioning
confidence: 98%
“…Human centromeric DNA contains the 17-bp "CENP-B box," which directly recruits the centromere protein CENP-B (Masumoto et al 1989). CENP-B knockout mice are for the most part phenotypically normal (Hudson et al 1998;Kapoor et al 1998;Perez-Castro et al 1998) and functional neocentromeres lack CENP-B (Saffery et al 2000). Moreover, CENP-B is absent from the human Y chromosome (Earnshaw et al 1987) and no CENP-B functional homologs have been identified in Xenopus, zebrafish, C. elegans, or Drosophila to date.…”
Section: Histone Modificationsmentioning
confidence: 99%